Design and Implementation of a Biologically Inspired Flying Robot - An EPS@ISEP 2014 Spring Project - Caramin, Bénédicte Anki (2015)
The goal of this EPS@ISEP project proposed in the Spring of 2014 was to develop a flapping wing flying robot. The project was embraced by a multinational team composed of four students from different countries and fields of study. The team designed and implemented a robot inspired by a biplane design, constructed from lightweight materials and battery powered. The prototype, called MyBird, was built with a 250 € budget, reuse existing materials as well as low cost solutions. Although the team's initial idea was to build a light radio controlled robot, time limitations along with setbacks involving the required electrical components led to a light but not radio controlled prototype. The team, from the experience gathered, made a number of future improvement suggestions, namely, the addition of radio control and a camera and the adoption of articulated monoplane design instead of the current biplane design for the wings.